Isolation of A New Sterol from Limonium stocksii and Antimicrobial Activities of Crude Extract - Rahat A. Ali,; Shaheen Inam ,; Shaista Perveen, (Journal of Basic & Applied Sciences, 2013)
A new sterol was isolated from the leaves of Limonium stocksii, together with two other known sterols. The structure of new sterol was determined to be 3-Oxo-23-α-hydroxy methyl stigmasta-4-ene on the basis of spectroscopic evidences.